2007
DOI: 10.1590/s1516-93322007000200007
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of chlorogenic acid, caffeic acid and caffeine in hydroalcoholic and aqueous extracts of Ilex paraguariensis by HPLC and correlation with antioxidant capacity of the extracts by DPPH· reduction

Abstract: A new high performance liquid chromatographic method has been established for simultaneous determination of chlorogenic acid, caffeic acid and caffeine in hydroalcoholic and aqueous extracts ofIlex paraguariensis. Analytical curves showed good linear regression in the concentration ranges 0.49-7.8 μg/mL for chlorogenic acid, 0.25-3.9 μg/mL for caffeic acid and 0.244-7.8 μg/mL for caffeine. Reduction of the DPPH· radical was used to determine the antioxidant capacity of the extracts. Our method for the simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…Moure et al (2001) showed that the stability of polyphenol compounds during the extraction and dehydration is affected by chemical and enzymatic degradations, by the volatilization of compounds and mainly by the thermal decomposition. Rivelli et al (2007) Brasil 1996). Figure 1a presents the pH values of the different formulations tested in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Moure et al (2001) showed that the stability of polyphenol compounds during the extraction and dehydration is affected by chemical and enzymatic degradations, by the volatilization of compounds and mainly by the thermal decomposition. Rivelli et al (2007) Brasil 1996). Figure 1a presents the pH values of the different formulations tested in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Mate is used for its central nervous system stimulant properties, which are due to the presence of the methylxanthines caffeine and theobromine (Blumenthal and Brinckmann, 2000;Dermarderosian, 2001;Filip et al, 1998). Additionally, yerba-mate is also considered a functional food, because of its nutritional and medicinal properties, such as hypocholesterolemic, hepatoprotective, diuretic, and antioxidant properties (Bixby et al, 2005;Filip et al, 2000;Gugliucci and Stahl, 1995;Heck and De Mejia, 2007;Rivelli et al, 2007;Valerga et al, 2012), which can protect against the harmful effect of free radicals, thereby increasing the defense system of the organism. It can also help prevent atherosclerosis and coronary heart disease (Heck and De Mejia, 2007;Miranda et al, 2008;Puangpraphant and de Mejia, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The HPLC method used in this study to quantify HMF, CQA and caffeine in CS extracts was based on the work of Lemos et al (2010) and Rivelli et al (2007). The chromatographic analysis was per-formed in a HPLC integrated system (Jasco, Japan) equipped with a PU-980 pump and a Jasco AS-950 automatic sampler with a 20 µL loop.…”
Section: Analysis Of Caffeine Hmf and Cga Content In Episkin Tmmentioning
confidence: 99%